2020
DOI: 10.1080/08998280.2019.1710658
|View full text |Cite
|
Sign up to set email alerts
|

Relation between mean platelet volume and C-reactive protein

Abstract: Mean platelet volume (MPV) is a measure of platelet activation, and C-reactive protein (CRP) is an established marker of inflammation. Studies on the correlation between MPV and CRP have produced ambiguous results. We undertook a population study with the National Health and Nutrition Examination Survey (NHANES) data (2005)(2006)(2007)(2008)(2009)(2010) to investigate the relationship between CRP and MPV. CRP was analyzed both as a continuous variable and as a categorical variable (low, intermediate, or high).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In addition, IBD patients suffer from anemia due to poor intestinal absorption or intestinal bleeding. 44 In this study, a significant increase in HGB, RBCs, and HCT was observed after the PCO treatment, suggesting the ameliorative effect of PCOs on anemia in the colitis mice (Fig. 1I–K).…”
Section: Discussionsupporting
confidence: 60%
“…In addition, IBD patients suffer from anemia due to poor intestinal absorption or intestinal bleeding. 44 In this study, a significant increase in HGB, RBCs, and HCT was observed after the PCO treatment, suggesting the ameliorative effect of PCOs on anemia in the colitis mice (Fig. 1I–K).…”
Section: Discussionsupporting
confidence: 60%
“…In clinical practice, MPV could be used as an indicator for the early diagnosis of neonatal sepsis [15,[20][21][22][23]. Several studies have examined the potential correlation between CRP and MPV values in patients with inflammatory states [24][25][26][27]. But only one study investigated the CRP/MPV ratio in children with pneumonia [28].…”
Section: Introductionmentioning
confidence: 99%
“…MPV was found to be negatively correlated with ESR and CRP in patients with rheumatoid arthritis and inflammatory bowel disease [26,27]. However, the largest study about the relation between MPV and CRP come from a population study of National Health and Nutrition Examination Survey (NHANES) data in 16,329 subjects revealing a significant negative correlation between MPV and CRP [28].…”
Section: Discussionmentioning
confidence: 99%